Analysis of Product Label Prices in Determining Sales at Alfamidi Dawuan Cikampek - Nureli Padilah; Dedi Mulyadi; Santi Pertiwi Hari Sandi (West Science Business and Management, 2024)
The development of the modern retail business is currently growing rapidly and has spread throughout Indonesia. Currently around us we can see various modern retail stores such as Alfamart, Indomart, Supermarkets and other modern stores that have appeared in residential areas near the community. Tabanan Regency is one of the provincial governments in Bali where there are many retail businesses like today, especially in the Kerambitan area. The price tag is the product price printed on the front of the object. Price labels act as a tool for consumers to more easily see the price of the product they are buying and directly see the price of the product listed on the shelf. This research aims to analyze product price labels in determining sales at Alfamidi Dawuan Cikampek. This research method is the Qualitative Descriptive method, which is a research method used to examine the condition of natural objects. Data collection techniques were collected by observation, interviews and documentation. Data analysis through data presentation, Based on research data from October-December 2023, it shows that the month with the best product sales achievements is the product that is always included in the price label product list with the highest sales achievements of the 5 products during the last 3 months.